Peta 3D Desa Muncan Dengan Augmented Reality Berbasis Marker - Lalu Atasaldi; Saeful Hamdi; Ichwan Purwata (Explorer, 2022)
Augmented reality is a technology that combines 2D or 3D virtual objects into a real environment. Augmented Reality can be used in various fields, one of which is used for the introduction of an area with 3D forms. Muncan Village has an area of ​​± 325,180 ha/m2, regarding the area and boundaries of Muncan Village, the residents of Muncan Village have difficulty finding houses for the hamlet head, schools, mosques or the potential in other hamlets. Likewise with residents outside Muncan Village who will look for a product in Muncan Village. There are also places of economic, tourism and cultural sources in Muncan Village whose location is rarely the residents of Muncan Village themselves know their location. In this case, information media is needed that can provide instructions and display strategic places and the potential that exists in each hamlet in Muncan Village in the form of a 3D Map with Augmented Reality technology with the aim of making it look more real and can be accessed anywhere via a smartphone.